2016
DOI: 10.32598/ijt.10.1.88.6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and Chitosan Alleviate Toxic Effects of Paraquat on Some Biochemical Parameters in Hepatocytes of Common Carp

Abstract: Background: Paraquat is nonselective bipyridyl herbicide that induces hepatotoxicity through oxidative stress. Vitamin C and chitosan have antioxidant as well as radical scavenger properties and show protective effects against reactive oxygen species (ROS). In the present study, hepatoprotective effects of chitosan and vitamin C were evaluated in common carp exposed to paraquat. Methods: While exposed to 0.02 mg. L-1paraquat for 21 days, common carp were fed chitosan (1000 mg. kg‑1 feed), vitamin C (1000 mg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In this study, it was found that vitamin C is effective in decreasing the hepatotoxicity of paraquat. However, concomitant use of chitosan and vitamin C is more effective and has a synergistic effect and can be used to protect the liver against paraquat in carp [22] . In 2012, a study by Eatemad examined the morphological changes in rat liver tissue after receiving paraquat, and examined the protective effect of vitamin C in improving paraquat‐induced tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was found that vitamin C is effective in decreasing the hepatotoxicity of paraquat. However, concomitant use of chitosan and vitamin C is more effective and has a synergistic effect and can be used to protect the liver against paraquat in carp [22] . In 2012, a study by Eatemad examined the morphological changes in rat liver tissue after receiving paraquat, and examined the protective effect of vitamin C in improving paraquat‐induced tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, concomitant use of chitosan and vitamin C is more effective and has a synergistic effect and can be used to protect the liver against paraquat in carp. [22] In 2012, a study by Eatemad examined the morphological changes in rat liver tissue after receiving paraquat, and examined the protective effect of vitamin C in improving paraquat-induced tissue damage. Histopathological examination showed improvement of liver tissue cells in rats receiving vitamin C compared to untreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…We know very well that exposure of fish to xenobiotics such as herbicides could cause an imbalance between ROS contents and cellular antioxidant defense capacity [32]. Therefore, exposure of fish to herbicides could lead to oxidative stress.…”
Section: Detoxification and Metabolism Of Herbicidesmentioning
confidence: 99%
“…Moreover, the rapture of cellular membranes may cause the release of cytoplasmic contents or organelles into intercellular fluid such as serum. Hence, assessing biochemical parameters in serum can indicate the stability of cellular membranes after exposure to herbicides [32]. Geetha [40] demonstrated that exposure to Roundup® could affect the balance of plasma electrolytes and transaminase activity in L. rohita [40].…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
“…Multiple studies have shown evidence that the combination of vitamin C and VC with chitosan offers protection to fish against the harmful effects of CdCl2 on various biochemical markers in liver tissues. In their study, Sharifinasab et al (2015) examined the potential of Vitamin C and Chitosan to mitigate the toxic effects of paraquat on several biochemical parameters in hepatocytes of Common carp. The researchers found that the administration of vitamin C was successful in lowering the liver toxicity induced by paraquat.…”
Section: Advantages Of Vitamin C In Aquaculturementioning
confidence: 99%